Association of polymorphism rs12329760 of the TMPRSS2 gene with coronavirus infection - Bisseneva, A.K.; Погосян, Г.П.; Ли, К.Г. (Fundamental and Experimental Biology, 2023)
The article presents the results of genotyping of DNA samples obtained from study participants with the established status of coronavirus infection (COVID-19) using enzyme immunoassay for the single nucleotide polymorphism rs12329760 (C/T) of the TMPRSS2 gene. Genotyping was carried out by polymerase chain reaction (PCR) in real time using the technique “Amplification of the refractory mutation system” (ARMS). The distribution of frequencies of genotypes and alleles rs12329760 C>T of the TMPRSS2 gene in 80 people of the experimental and control groups was analyzed. The presence of the significance of the single nucleotide polymorphism rs12329760 of the TMPRSS2 gene in the homozygous state ( CC) and heterozygous (CT) and the absence of the significance of the TT genotype was found. A statistically significant difference in the distribution of the T allele was found.